2013
DOI: 10.1016/j.gaitpost.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered postural sway persists after anterior cruciate ligament reconstruction and return to sport

Abstract: Postural sway is defined as the movement of a body’s center of mass within the base of support to maintain postural equilibrium. Deficits in postural sway are present after ACL injury; however, current evidence linking it to future injury risk is unclear. The purpose of this study was to determine if postural sway deficits persist after ACL reconstruction (ACLR). The hypothesis tested was that after ACLR, patients who return to sport (RTS) would demonstrate differences in postural sway compared to control (CTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 25 publications
(46 reference statements)
1
45
0
1
Order By: Relevance
“…Owing to these functional impairments and clinical significance, patients with an ACL-deficient knee often choose to have reconstruction surgery, and the number of reported ACL reconstruction surgery cases is as high as 350 000 annually in the USA alone. 6 Although ACL reconstruction surgery has a high success rate, younger and more physically active individuals have a relatively high rate of reinjury, 7 which ranges from 24% 8 to 29% 9 along with strength deficits, 10 reduced postural control 1112 and altered kinematics. 1314 Furthermore, a systematic review that synthesised a total of 31 studies indicated that 48% of knee osteoarthritis prevalence rates more than 10 years following ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these functional impairments and clinical significance, patients with an ACL-deficient knee often choose to have reconstruction surgery, and the number of reported ACL reconstruction surgery cases is as high as 350 000 annually in the USA alone. 6 Although ACL reconstruction surgery has a high success rate, younger and more physically active individuals have a relatively high rate of reinjury, 7 which ranges from 24% 8 to 29% 9 along with strength deficits, 10 reduced postural control 1112 and altered kinematics. 1314 Furthermore, a systematic review that synthesised a total of 31 studies indicated that 48% of knee osteoarthritis prevalence rates more than 10 years following ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Lower balance-error scores were found in the ACL-reconstructed population than in a healthy control group. 6 Another study reported limited single-leg postural sway ability compared with the noninvolved side and healthy control.…”
Section: Resultsmentioning
confidence: 92%
“…6 Another study reported limited single-leg postural sway ability compared with the noninvolved side and healthy control. 7 The observed joint-position-accuracy differences from the reviewed studies ranged from 0.07° to 2.20°. Although the observed joint-position-sense difference was small between braced and nonbraced conditions, this difference may have had a clinical implication.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The following covariates were included in the analysis and were selected due to prior literature suggesting an effect on postural control: sex [31], age [32], BMI [11], ankle injury history [33], knee injury history, [34] and migraine history [35]. …”
Section: Statistical Analysesmentioning
confidence: 99%